Algorytmy sterowania jednostopniowymi węzłami ciepłowniczymi wspomaganymi instalacjami kolektorów słonecznych = Algorithms of regulation and control of one-stage district heating substations assisted by solar collector installations - Ziembicki, Piotr; Bernasiński, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The publication presents a technological schemes of one-stage district heating substations assisted by solar collector installations. In the paper was presented a scenarios of work of this installations depending on various parameters, including heat energy demand, intensity of solar radiation and characteristics of domestic hot water installation and domestic heating systems. The authors proposes an algorithms of regulation and control of district heating substations and defines a conditions of work of basic regulation subsystems.
Keywords: węzły ciepłownicze; energia odnawialna; kolektory słoneczne; sterowanie; automatyka regulacyjna; algorytmy sterowania; district heating substations; renewable energy; solar collector; control; control devices; control algoritms